EFEKTIVITAS DEWAN PERWAKILAN RAKYAT DAERAH DALAM MENJALANKAN FUNGSI PEMBENTUKAN PERATURAN DAERAH DAN FUNGSI PENGAWASAN (Qawanin Jurnal Ilmu Hukum, 2022)
ABSTRACThis study aims to determine and analyze the role of the local people's representative council in Bitung City in carrying out the functions of forming regional regulations and supervisory functions. The research method used in this paper is an empirical method, with coverage of primary data and secondary data, the research is carried out in the field, namely at the Office of the Regional People's Representative Council of Bitung City. The results of this study indicate that the Bitung City Regional People's Representative Council in carrying out its role is based on the Bitung City DPRD ordinance Number 1 of 2019 Article 23 paragraph (2) so that in its role in carrying out its functions, the DPRD remains on its way. So far, the Bitung City DPRD has taken part in the process of forming regional regulations, just like the Bitung City DPRD when it took steps to set the planning agenda for the preparation of regional regulations, of course with steps that were prepared in a planned, integrated and systematic manner. is part of this supporting institution in supporting the realization of the implementation of the legislative function which is a vital function attached to the legislative and executive organs. So that the Bitung City DPRD must actively discuss a draft regional regulation which will later be enacted or numbered at the provincial level. Not only that, the DPRD is also responsible for regional regulations that have been ratified with steps taken such as participating in socializing to the local community, so that the implementation of these regional regulations can be maximized and in accordance with the expectations of the parties who initiated the regulation.